2017
DOI: 10.1038/s41598-017-02007-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of FoxO1 and apoptosis in pulmonary vascular remolding in a rat model of chronic thromboembolic pulmonary hypertension

Abstract: To explore the role of FoxO1 and apoptosis in a rat model of chronic thromboembolic pulmonary hypertension (CTEPH). Rats were randomly divided into a sham group (n = 45) and an experimental group (n = 45). Autologous blood clots were injected into rats three times to induce CTEPH. Rats were further divided into three subgroups: a 1-week subgroup (n = 15), a 2-week subgroup (n = 15), and a 4-week subgroup (n = 15). Mean pulmonary arterial pressure (mPAP) and histopathology were evaluated at each time point. Fox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
(26 reference statements)
0
31
0
2
Order By: Relevance
“…In pulmonary artery remodelling, FOXO1 expression is decreased, which leads to Bad upregulation and Bcl-2 downregulation, two key proteins regulating programmed cell death. This interplay between FOXO1 and apoptosis in ECs may be a possible mechanism leading to pulmonary artery remodelling, as apoptotic ECs lose their ability to control smooth muscle proliferation [ 42 ]. Finally, FOXO1 promotes sprouting and migration of LECs, by enhancing the expression of the purigenic receptor P2RY1 in response to exogenous ATP [ 43 ].…”
Section: Metabolic Pathways and New Therapeutic Targets In Ecsmentioning
confidence: 99%
“…In pulmonary artery remodelling, FOXO1 expression is decreased, which leads to Bad upregulation and Bcl-2 downregulation, two key proteins regulating programmed cell death. This interplay between FOXO1 and apoptosis in ECs may be a possible mechanism leading to pulmonary artery remodelling, as apoptotic ECs lose their ability to control smooth muscle proliferation [ 42 ]. Finally, FOXO1 promotes sprouting and migration of LECs, by enhancing the expression of the purigenic receptor P2RY1 in response to exogenous ATP [ 43 ].…”
Section: Metabolic Pathways and New Therapeutic Targets In Ecsmentioning
confidence: 99%
“…As it is difficult to obtain the tissue of the human pulmonary artery, most of the studies on CTEPH are at the animal level. [19][20][21] In our previous studies, we performed the gene chip analysis of miRNA, lncRNA, and mRNA using the tissue of pulmonary arteries obtained from the CTEPH patients who underwent pulmonary endarterectomy, and the lung cancer patients who underwent pulmonary lobectomy. [14][15][16] However, the relationships between miRNA, lncRNA, and genes were not analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to DNA methylation, the role of aberrant transcription factor expression has thus far only been studied by one group [74,75]. In 2016, Deng and colleagues used a rat model in which CTEPH was induced by repeated injection of blood clots into the jugular vein, to investigate the expression of the transmembrane glycoprotein tissue factor (TF) and the transcription factor forkhead box transcription factor O-1 (FoxO1) [74].…”
Section: Transcription Factor Foxo1mentioning
confidence: 99%
“…In addition to the negative correlation with TF, FoxO1 levels also showed a trend towards a negative correlation with mean pulmonary artery pressure (mPAP), but any underlying mechanisms were not investigated in this study. However, in a second study published later in 2016 [75], the same group showed that together with the decrease of FoxO1 expression in the four-week period of CTEPH development, anti-apoptotic Bcl-2 also decreased, while pro-apoptotic Bad levels were increased in the PAECs. In addition, Bcl-2 levels negatively correlated with mPAP, and Bad levels showed a positive correlation with mPAP.…”
Section: Transcription Factor Foxo1mentioning
confidence: 99%